Morphometric Characteristics of Pyloric Gastric Glands at Experimental Acute Gastritis and after Administration of ‘Platex-Placental’ Medication on the Background of Experimental Acute Gastritis - Bilash, Sergiy M. (Problems of Cryobiology and Cryomedicine, 2013)
The study descrides the dynamics of changes in average indices of pyloric gastric glands at experimental acute gastritis, after administration of ‘Platex-Placental’ medication, and after administration of ‘Platex-Placental’ medication on a background of experimental acute gastritis. The positive outcomes were found after administration of ‘Platex-Placental’ medication in terms of inflammation course as well as reorganization of defence peculiarities of pyloric glands as a response to an acute inflammation.Probl Cryobiol Cryomed 2013; 23(1):84–90.